(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): This article explores the importance of intellectual capital in the company. Purpose: To determine what is the importance of intellectual capital in businesses in the current economic climate. Method: As a research method I used descriptive method, and review of the literature in the form of articles and books. Below I summarize important observations and insights. Results: Intellectual capital has a significant and positive impact on the business performance of the company, but it is underestimated. Organization: The research contributes to a better achievement of business performance. Society: Better business contributes to the wider environment, as this will also ensure stability of the organization. Originality: A different perspective on the importance of intellectual capital. There are not a lot of transparent articles on this topic. Limitations/Future Research: Limitation of the study is that we have discussed only a certain number of resources.